44.3k views
2 votes
Find the equivalent expression using the same bases (46 x 59)^6

2 Answers

4 votes

Answer:
46^6* 59^6

Explanation:

Given the expression
(46* 59)^6, in order to find an equivalent expression using the same bases, you need to remember the following:


(a*b)^n=a^n*b^n

So, you can observe that, in this case:


a=46\\b=59\\n=6

Therefore, substituting values, you get the following equivalent expression:


(46* 59)^6=46^6* 59^6

User Dhondup
by
4.8k points
4 votes

Answer:

46^6 x 59^6

Explanation:

For properties (axb)^y has the equivalent expression of a^y x b^y

Then, (46x59)^6 can be written as 46^6 x 59^6

User Vasanth Nag K V
by
6.0k points